Occupational Safety and Health Risks (K3) on Construction Workers Construction of the Four Floor Boarding House for Jalan Andong Barat - fifi damayanti; Yurnalisdel Yurnalisdel; Lucius Wato Koten (CV. Creative Tugu Pena, 2025)
The rapid growth of the modern industry requires employees to work with maximum performance and productivity in the middle of the work schedule that is dense safety and health in the workplace (K3) is important to protect workers from the dangers and risks at work, both physical, mental, and emotional. This study aims to evaluate the application of Occupational Safety and Health (K3) in the Four -Floor Boarding House Construction Project on Jalan Andong Barat. The research method uses a quantitative descriptive approach by collecting data through observation of the use of personal protective equipment (APD) for 14 days. Data were analyzed using SPSS to identify the level of compliance, the trend of using PPE, and the factors that influence K3. Based on the calculation of the average compliance level of PPE use in the work structure of lightweight steel roof frame structures in the four-storey boarding house of Jalan Andong Barat for 14 days is 70%. Based on PU/PR Regulation No. 09/2008, this figure is included in the category of moderate compliance (60-85%) while the type of PPE with a very good use rate (≥85%) is a helmet (95%), glasses (86%), boots (95%), and work clothes (100%) while the type of PPE with a fairly good use rate (60-85%) is glove (41%), Safety Belt (51%), Ear Protector (51%), and Full Body Harness (34%). The results show that the use of PPE such as helmets (95%), safety shoes (95%), and work clothes (100%) have met the standard, while Full Body Harness (34%) and masks (41%) are still low. Conclusion This study emphasizes the importance of increasing OHS training and strict supervision of the use of PPE, especially for equipment with low compliance levels